Russia Teachers : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents results of the application of SABER teachers in three administrative divisions of Russia. It describes the performance of Tomsk oblast, Ivanovo oblast, and St.Petersburg in each of the eight teacher policy goals, alongside comparative information from education systems.